2002
DOI: 10.1002/jsfa.1132
|View full text |Cite
|
Sign up to set email alerts
|

Low‐salt restructured fish products using microbial transglutaminase as binding agent

Abstract: Low-salt restructured silver carp products were obtained using mechanically deboned ®sh meat from ®lleting wastes of silver carp (Hypophthalmichthys molitrix). The additives used were NaCl at three levels (0 (control), 10 and 20 g kg À1 ) and microbial transglutaminase (MTGase) also at three levels (0 (control), 3 and 6 g kg À1 ). The ®sh meat was massaged with the additives at <15°C for 1 h. The massaged ®sh paste was then packed into steel stainless tubes and cooked at 40°C for 30 min followed by 90°C for 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
3
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 21 publications
5
49
3
3
Order By: Relevance
“…Nevertheless, when adding TG, color deterioration was observed. TG was also used in restructured fish, such as silver carp products Te´llez-Luis, Uresti, Ramı´rez, & Va´zquez, 2002).…”
Section: Soy Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, when adding TG, color deterioration was observed. TG was also used in restructured fish, such as silver carp products Te´llez-Luis, Uresti, Ramı´rez, & Va´zquez, 2002).…”
Section: Soy Proteinsmentioning
confidence: 99%
“…Tsai, Unklesbay, Unklesbay, and Clarke (1998) concluded that the textural characteristics were highly affected by binders, heating temperature, and their interaction. Te´llez-Luis et al (2002) found it is feasible to obtain low-salt restructured silver carp production with improved textural and functional properties using 3 g/kg TG and 10 g/kg NaCl as protein binders.…”
Section: Protein Bindingmentioning
confidence: 99%
“…MTGase catalyzes the same reaction as endogenous transglutaminase, but the first is non-calcium dependent and shows lower deamidation affinity than endogenous transglutaminase of fish (Ohtsuka et al, 2001;Sato et al, 2001). Several studies have been conducted to determine the optimal conditions for using MTGase in restructured fish products (Zhu et al, 1995;Téllez-Luis et al, 2002;Uresti et al, 2004;Ramírez et al, 2007). The objective of this work was to determine the feasibility of using microbial transglutaminase (MTGase) as binding agent to prepare a restructured fish products from white croacker mince with acceptable sensorial characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…From the public health point of view, the partial replacement of salt with other binding agents is recommended because a reduction in salt intake can help prevent and control hypertension (Sebranek et al, 1983). Development of no or low-salt meat and fish-based products have been attempted by various investigators (Vareltzis, 1988;Hennigar et al, 1989;Vareltzis et al, 1989;Nahrinen et al, 1998;Tėllez-Luis et al, 2002). In an attempt to reduce salt level in such products, a method for restructuring meat using food proteins as a substrate of MTG was studied (Kuraishi et al, 1997) and it was concluded that MTG-sodium caseinate system could serve as a real cold-set binder to produce restructured meat in the raw, refrigerated state without addition of NaCl.…”
mentioning
confidence: 99%
“…According the above researchers, caseinate was effective in increasing formation of G-L bonds by MTG due to its substrate specificity. Several studies dealing with the feasibility of using MTG as cold-set binder (at temperature <10˚C) to obtain restructured meat (Kuraishi et al, 1997;Kerry et al, 1999;Ruiz-Carrascal and Regenstein, 2002;Carballo et al, 2006;Cofrades et al, 2011), and fish products Tėllez-Luis et al, 2002;Suklim et al, 2004;Tėllez-Luis et al, 2004;Moreno et al, 2009;Gonçalves et al, 2010;Moreno et al, 2010;Andrés-Bello et al, 2011) have been reported during the last decade. Mediterranean horse mackerel, an abundant fish species in Greece, remain an underutilized marine resource.…”
mentioning
confidence: 99%